Prosedur pengendalian inkues oleh koroner di Malaysia: Satu kajian perundangan / Noorfajri Ismail - Noorfajri , Ismail (2018)
Inquiries of death or inquest by coroner is a mechanism to investigate the cause of death in order to bring justice to the deceased and their kins. Inquest is a process which is inquisitorial in nature with the coroner being a judicial investigator, however is the conduct of inquest in Malaysia effective? It is submitted that the inquest practice and procedure in this country is ineffective and is more complex and complicated with the recent development of court cases. The purpose of this research is to identify the actual role of a coroner in handling inquest. The development of mechanism under common law in England and Wales is also analysed which includes governance, practice and procedures. Comparative research on the mechanism showed that a lot of development had occurred which can be considered to be applied in Malaysia, in addition the best solution in providing an effective death investigation institution is through statutory reform. For this purpose, a study on the comparative statutory development inclusive of the adoption of ‘European Jurisprudence’ in British coroner’s legal system in England and Wales which has significantly changed the landscape of coronial legislation in Victoria (Australia), is also included in this discussion. This comparative study shows the existence of interdisciplinary interaction between the coroner’s investigations as a public health mechanism in a unique scope of procedural judicial framework, not just to identify the true cause of death but also capable of preventing possible recurrence.